Report in the daily experience of early childhood education - Eliane M. M. Madureira; Eveland Deiconclili Caetano; Fabiana Meurer Silvino (Universidade Federal de Santa Catarina, 2000)
On a sunny afternoon, we walked in the "forest" with the children and teacher. The "forest", named by children, was nothing more than a piece of land next to the Creche "Fermínio Francisco Vieira" in the stream Grande, Florianópolis, where a group of interns is experiencing its practice.